Flow properties of Cu/CNTs feedstocks - ., Ali Samer Muhsan, Faiz Ahmad, M Rafi Raza (2011)
In this study, the flow behavior of multi-walled carbon nanotubes (CNTs) reinforced copper matrix feedstocks is presented. The solid loadings in the copper feedstock were investigated in the ranges of 55-61 Vol.% using binder. Pure copper (Cu) and Cu/CNTs feedstocks were compounded using internal mixer machine for homogenous dispersion of solids in the binder. The flow behavior were measured using a capillary rheometer in the shear rate range expected to occur during powder injection molding. An acceptable increasing trend in viscosity of the copper feedstock with powder loading was recorded. Cu/CNTs composite feedstocks showed viscosity more than 1000 Pa.s which is most probably due to the addition of CNTs and increasing trend in viscosity of Cu/CNTs was noted as well. The results also identified that the feedstock containing 59 vol.% copper was most suitable for substitution of CNTs in Cu feedstock.